Effects of Isentropic Efficiency and Enhancing Strategies on Gas Turbine Performance - Thamir K., Ibrahim; M. M., Rahman (Faculty Mechanical Engineering, UMP, 2013)
Owing to their numerous advantages, gas turbine (GT) power plants have become an important technology for power generation. This paper presents a parametric analysis for different configurations of GT plants, considering the effects of isentropic compressor and turbine efficiency, which allows the selection of the optimum GT configuration for the optimum performance of a GT power plant. The computational model was developed utilizing MATLAB software. The simulated results show that the reheat GT configuration has higher power output, whereas the regenerative GT configuration has higher thermal efficiency, when considering the effects of isentropic compressor and turbine efficiency. The maximum thermal efficiency of 52.4% and the maximum power output of 268 MW are obtained with isentropic turbine efficiency. The result reveals that isentropic compressor and turbine efficiency influence significantly the performance of GTs.